Methodology for locating regional landfills using multi-criteria decision analysis techniques. Issue 1 (1st January 2020) - Manyoma-Velásquez, Pablo César; Vidal-Holguín, Carlos Julio; Torres-Lozada, Patricia
Abstract: In Latin American and Caribbean countries, many landfills are nearing the end of the life cycle. The expectations of multiple stakeholders (the community, the government, non-governmental entities, among others) generate greater complexity to the problem of locating new sites. Decisions on the location of these landfills require the consideration of numerous criteria that must be evaluated simultaneously as a whole. The main objective of this research is to propose a methodology to identify the best locations for regional landfills. Through the literature review, seven (7) criteria have been defined that cover the environmental, social and financial needs of this decision type. Within framework of a selected region with 20 municipalities, approximately 1, 200, 000 inhabitants and an annual generation of 233, 000 tons of waste, 5 possible sites were found that were analyzed under two multi-criteria methodologies: analytical hierarchy process (AHP) and the technique to order the preference for similarity with the ideal solution (TOPSIS). Preference for combination of possible sites was one of the main results. This may allow the rulers to design different strategies to make agreements with the communities involved near these new sites. Likewise, through a sensitivity analysis it was possible to verify the importance that the modification of fares (transport and disposal) may have on the result, converting an alternative as the best, without having been it at the beginning. This research is expected to be a planning tool for local governments that allows them to think about the future of their regions.